S-210JA-20 21 ゴウキ ニヨル デンシ ミツド オンド カンソク ケッカ e. イベント セッション ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 2 - 宮崎, 茂; ミヤザキ, シゲル; 森, 弘隆; モリ, ヒロタカ; 小川, 忠彦; オガワ, タダヒコ; MIYAZAKI, Shigeru; MORI, Hirotaka; OGAWA, Tadahiko (1980)
P(論文) S-210JA-20および21号機により電離層じょう乱時の電子密度・温度プロファイルを測定した.前者では,E_S層の電子密度増加を示し,高度115kmにおいて約5×10^5/cm^3,電子温度が高度100km付近で約1100Kを示すことが観測された.後者では高度110kmにおいて電子密度約2×10^5/cm^3および高度110kmにおいて電子温度約1000Kを観測した. Two sounding rockets, S-210JA-20 and 21, were launched into the disturbed ionosphere from Syowa Station, Antarctica, in the winter of 1976 for measuring electron density and temperature. Enhancement of the E region electron density of about 5×10^5/cm^3 at 115 km and the electron temperature of about 1100 K around 100 km were observed by S-210JA-20. Maximum electron density of about 2×10^5/cm^3 around 110 km and the electron temperature of about 1000 K around 110 km were observed by S-210JA-21. departmental bulletin paper